Sepsis in Children with Acute Lymphoblastic Leukemia - Mururul Aisyi; Fifi Dwijayanti; Reni Wigati; Haridini Intan Mahdi; Laswita Yunus; Chainurridha Chainurridha; Tri Aprilliana Wulandari (Indonesian Journal of Cancer, 2020)
Background: Sepsis is the leading cause of morbidity and mortality in children worldwide, with around 75,000 inpatients each year and nearly 50% dying in pediatric hospitals. Acute lymphoblastic leukemia (ALL) in childhood is a malignancy originating from lymphoid progenitor cells, usually at the age of 2–6 years. Children with ALL contribute 30% to childhood cancer cases under 15 years old. Sepsis in pediatric patients increases mortality significantly. A previous study showed that the prevalence of sepsis in pediatrics is still high. Thus, this study aims to report ALL patients with sepsis in our institution.Methods: This study was a descriptive cross-sectional study at the National Cancer Center (NCC) - Dharmais Cancer Hospital. We recruited acute lymphoblastic leukemia (ALL) patients aged 2-18 years with suspected or documented sepsis based on Systemic Inflammatory Response Syndrome (SIRS) by The International Consensus Conference on Pediatric Sepsis. The data were collected by medical records from January 2014 to December 2018.Results: A total of 94 pediatric patients in the study included 57 males and 37 females with an average age of 5 years. The age range was 1–18 years with a median age of 5 years. The prevalence of sepsis in pediatric with ALL was 11 patients (11.7%) and 45.5% of deaths. The clinical conditions were as follows: abnormal temperature (8 [72.7%]), abnormal blood pressure, systolic (7 [63.6%]) and diastolic (7 [63.6%]), abnormal pulse rate (9 [81.8%]), abnormal respiratory rate (8 [72.7%]), and normal saturation (6 [54.5%]). We also did a laboratory check followed by all sepsis patients who had abnormal leukocytes (11 [100%]), and abnormal lymphocytes count (8 [72.7%]).Conclusions: The mortality rate and prevalence of sepsis in children with ALL in our institution are still high. Further prospective studies are required to explore the risk factors and predictors of sepsis based on its severity and adherence of health workers to implement guidelines on patients with sepsis in the hospital.